How long does it take? An analysis of volumetric image assessment time. Issue 1 (April 2016) - Li, Winnie; Jaffray, David A.; Wilson, Graham; Moseley, Douglas
Abstract: This work measured time taken to integrate image-guidance with CBCTs in routine clinical practice for patients treated between 2007 and 2010 across eight linear accelerators. 117, 301 CBCTs from 4592 patients across thirteen disease sites were included. The mean image assessment decision time was 79 s. Decision time was correlated with setup displacement magnitude.